How to be sort of happy in law school eaudiobook - Young, Kathryne M. (Tantor Media, 2018)
Each year, over 40,000 new students enter America's law schools. Each new crop experiences startlingly high rates of depression, anxiety, fatigue, and dissatisfaction. Kathryne M. Young was one of those disgruntled law students. After finishing law school (and a PhD), she set out to learn more about the law school experience and how to improve it for future students. Young conducted one of the most ambitious studies of law students ever undertaken, charting the experiences of over 1000 law students from over 100 different law schools, along with hundreds of alumni, dropouts, law professors, and more. How to Be Sort of Happy in Law School is smart, compelling, and highly engaging. Combining her own observations and experiences with the results of her study and the latest sociological research on law schools, Young offers a very different take from previous books about law school survival. Instead of assuming we should all aspire to law-review-and-big-firm notions of success, Young teaches students how to approach law school on their own terms: how to tune out the drumbeat of oppressive expectations and conventional wisdom to create a new breed of law school experience altogether. Young provides listeners with practical tools for finding focus, happiness, and a sense of purpose while facing the seemingly endless onslaught of problems law school presents daily. This book is an indispensable companion for today's law students, prospective law students, and anyone who cares about making law students' lives better. Bursting with warmth, realism, and a touch of firebrand wit, How to Be Sort of Happy in Law School equips law students with much-needed wisdom for thriving during those three crucial years.